2020
DOI: 10.1039/d0sm01247e
|View full text |Cite
|
Sign up to set email alerts
|

Creep attenuation in glassy polymer nanocomposites with variable polymer–nanoparticle interactions

Abstract: The addition of nanoparticles attenuates creep deformation in polymer nanocomposites; networked nanoparticle morphologies are more effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…This method for quantifying creep attenuation has been used previously and the exponential relation between critical time and NP loading are not qualitatively sensitive to the choice of critical compliance values. 10 We note that while t crit is small (< 100s) for this reference temperature, under ambient conditions (around 25 • C) t crit may be on the order of several 10s to 100s of years due to the timetemperature equivalence in polymer viscoelasticity. These results are in qualitative agreement with previous measurements of creep in P2VP-silica nanocomposites.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…This method for quantifying creep attenuation has been used previously and the exponential relation between critical time and NP loading are not qualitatively sensitive to the choice of critical compliance values. 10 We note that while t crit is small (< 100s) for this reference temperature, under ambient conditions (around 25 • C) t crit may be on the order of several 10s to 100s of years due to the timetemperature equivalence in polymer viscoelasticity. These results are in qualitative agreement with previous measurements of creep in P2VP-silica nanocomposites.…”
Section: Resultsmentioning
confidence: 73%
“…These results are in qualitative agreement with previous measurements of creep in P2VP-silica nanocomposites. 10 We also study the effects of polymer-NP interactions on creep suppression in simulation systems, by fixing the NP loading at 10 vol% and varying the interaction parameters between polymers and NPs. We find strongly interacting NPs better suppress creep, as evidenced by the shift of the upturn in compliance curves to a longer times and the increase in t crit with pn (Figure 2c and 2f).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the interactions in the system, many preparation conditions, such as the volume fraction of nanoparticles and the surfactants, will also affect the structure of PNCs 101 . Winey et al 102 added 5%–20% silica nanoparticles to the PS and P2VP solutions, respectively. And the results showed that the particles formed aggregations even adding the lowest number of nanoparticles.…”
Section: Nanoparticles Dispersion In Polymer Solutionmentioning
confidence: 99%